Recent Advances in Real‐Time Analysis of Electrochemical Reactions by Electrochemical Mass Spectrometry†. Issue 2 (10th December 2022) - Zhang, Xianhao; Zhan, Jirui; Yu, Zhengyou; Deng, Jintao; Li, Meixian; Shao, Yuanhua
Comprehensive Summary: Electrochemical mass spectrometry (EC‐MS) is a powerful tool to capture and analyze the intermediates and products during electrochemical reactions. This hyphenated technique combines electrochemistry with mass spectrometry using specific apparatuses, which helps researchers study mechanisms of redox reactions by in situ detecting chemical composition changes. Recently, various EC‐MS methods have been applied in a series of electrochemical reactions to reveal the mechanisms, mainly in the areas of electrochemical sensors, organic electrochemistry, and electrocatalysis. In this review, we intend to summarize the recent advances in real‐time analysis of different types of electrochemical reactions by EC‐MS and offer an outlook on the perspectives in these areas. Abstract : In this review, we introduce the recent advances in electrochemical mass spectrometry (EC‐MS) techniques and their applications in real‐time analysis and mechanism studies of reactions in electrochemical sensors, organic electrochemistry, and electrocatalysis. We hope this summary will attract the interest of scientists in related areas, who can cooperate and jointly promote the development of this interdisciplinary area.